Studying Application of Self Financing Methods in Autonomized Vietnam Public Universities - Giang, Ngo Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 4, 2019)
The study analyizes practical experience of funding sources of public universities in Vietnam, appraises structure of funding sources applied in autonomized Vietnam public universities; reviews funding experiences of public universities in other countries. Founded results shown that the public universities in Vietnam have mobilized funds from six sources as state budget, tuition and fee, endowment funds, amenity services, consulting services, researches and investment income. However, only three self financing sources of fund considered as subtainable, long maturity and interest rate flexibility are tuition and fee, services and investment income. Basing on analysing results, the research proposed methods to mobilize the funding sources.